Peran Otoritas Jasa Keuangan Dalam Pengawasan Jasa Layanan Keuangan Berbasis Financial Technology Peer to Peer Lending - Arifin, Zaenal; Lestari, Rohmini Indah; Saifudin, Saifudin; Putrisetia, Difa Ayu (Universitas Semarang, 2023)
This research aims to examine the regulation and supervision of the Financial Services Authority (OJK) regarding the provision of financial technology-based peer-to-peer lending services. The utilization of knowledge and technology in the financial sector is marked by the emergence of financial technology (Fintech). The presence of Fintech has brought convenience to various types of financial transactions. However, these positive impacts are not without their negative consequences. This is because many businesses establish or operate Fintech platforms without proper authorization or registration with the OJK. The regulation of Fintech itself is scattered across various legal provisions. This research method is normative juridical. The results of this study indicate a lack of comprehensive regulation, which has the potential to weaken legal protection for Fintech consumers. There is a need for comprehensive regulations addressing illegal Fintech activities and consumer protection in the Fintech sector. Optimal supervision of Fintech services will provide a sense of security for Fintech consumers and protect their rights. The OJK's supervision of Fintech has not been maximized, and illegal Fintech providers continue to emerge. Penelitian ini bertujuan mengkaji pengaturan dan pengawasan Otoritas Jasa Keuangan (OJK) terhadap penyelenggaraan jasa layanan keuangan digital berbasis financial technology peer to peer lending. Pemanfaatan ilmu pengetahuan dan teknologi dalam bidang keuangan ditandai dengan lahirnya financial technology (Fintech). Hadirnya Fintech membawa kemudahan di segala jenis transaksi keuangan. Namun dampak positif tersebut tidak lepas juga dari dampak negatif yang timbul. Hal ini terjadi karena banyak pelaku usaha yang mendirikan atau menjalankan Fintech tanpa adanya izin atau terdaftar di OJK. Pengaturan Fintech sendiri masih tersebar dalam berbagai peraturan perundang-undangan. Metode penelitian ini adalah yuridis normatif. Hasil penelitian ini adalah. Hasil penelitian ini adalah ketiadaan pengaturan yang komprehensif berpotensi mengakibatkan lemahnya perlindungan hukum bagi konsumen Fintech. Perlu adanya regulasi yang komprehensif terkait adanya Fintech ilegal dan juga perlindungan terhadap konsumen Fintech. Pengawasan yang optimal terhadap jasa layanan Fintech akan memberikan rasa aman untuk para konsumen Fintech dan dapat terlindungi hak-hak dari konsumen. OJK dalam melaksanakan pengawasan terhadap Fintech belum maksimal dan masih terus bermunculan penyelenggran Fintech ilegal.